Recommendations of the Resuscitation Council of Serbia for the implementation of resuscitation measures during the Covid 19 pandemic - Budimski, Mihaela; Lazić, Aleksandra; Josipovic, Mila; Fiser, Zoran; Obradović, Ivana (Journal Resuscitatio Balcanica, 2020)
The COVID 19 pandemic is caused by a virus we do not know enough about. The new situation has led to the need to enable quality resuscitation of patients with COVID 19 infection, but with quality protection of medical professionals from the risk of infection. Our efforts within our program activities are aimed at making recommendations to the Resuscitation Council of Serbia as the leading professional professional organization for the implementation of resuscitation measures in the conditions of the COVID 19 pandemic.We have made Recommendations for the implementation of resuscitation measures, Recommendations for ethical issues, the application of resuscitation measures in patients with COVID 19 infection and recommendations for training during the COVID-19 pandemic.We have made recommendations in cooperation with the European Resuscitation Council and other partner organizations, which are part of the network of national councils for resuscitation medicine in Europe.The recommendations will be modified in the coming period with the appearance of new knowledge and supplemented in relation to this basic text on the basis of new scientific evidence every 6 months until the adoption of unique recommendations of the European Resuscitation Council which are expected to be published in autumn 2021.
Keywords: cardicardiopulmonary resuscitation; ethics during resuscitation; resuscitation training; basic life support; advanced life support